Characterization of Bean Common Mosaic Virus (BCMV) strain Peanut Stripe Virus (PStV) associated with patchouli mottle disease in Indonesia - SEDYO HARTONO; ARGAWI KANDITO (Society for Indonesian Biodiversity, 2024)
Abstract. Hartono S, Kandito A. 2024. Characterization of Bean Common Mosaic Virus (BCMV) strain Peanut Stripe Virus (PStV) associated with patchouli mottle disease in Indonesia. Biodiversitas 25: 3860-3867. Patchouli (Pogostemon cablin Benth.) is an important commodity that is traded for its essential oil. Indonesia is the main producer of patchouli oil and provides 90% of the global oil trade. However, patchouli plantations face several constraints, especially plant diseases caused by viruses. Considering its economic importance, we conducted surveillance and detection of patchouli mottle disease (PMoD) in several patchouli plantations in Java. Leaves of infected plants exhibited symptoms of mosaic, mottling, and malformations. To confirm the presence of the virus, we collected the infected plants and mechanically inoculated it on healthy patchouli plants. This process involves applying the sap to healthy plants in a controlled manner to ensure that the symptoms observed in the field can be reproduced. Local lesions were produced on mechanically infected Chenopodium amaranticolor and Gomphrena globosa; systemic symptoms on Cucurbita maxima, Vigna unguiculata, Nicotiana tabacum, and Nicotiana glutinosa. Electron microscopic analysis of leaf-dip preparations from a symptomatic sample revealed flexuous viral particles sized approx. 750 nm long, identical to the Potyvirus virion. Molecular detection using RT-PCR and degenerate primers for Potyvirus produced 709 base pair amplicons, indicating positive results in our samples. Nucleotide sequencing data showed the sample was infected by Bean Common Mosaic Virus (BCMV) strain Peanut Stripe Virus (PStV), with high similarity to BCMV isolated from legume plants. To our knowledge, this is the first report of the natural occurrence of BCMV strain PStV on patchouli plants in Indonesia. Therefore, integrated pest management measures are needed to control the disease and reduce the economic impact of PMoD.